Wujud Dekonstruksi Jacques Derrida dalam Novel Carita Calin Karya Aprilia Fatmawati - Rahma Mardiana Kurniasih (Haluan Sastra Budaya, 2024)
This study aims to examine a form of deconstruction contained in the novel Carita Calin by Aprilia Fatmawati. Bringing marginalized meaning to content to make it look equal. This study consists of two problem formulations taken from just two concepts from Derrida's deconstruction theory, namely binary opposition and new construction of the main character. The purpose of this study is to describe the work of binary opposition and new constructions related to the main character, namely Calin, in the novel Carita Calin by Aprilia Fatmawati. The approach used in this study is the deconstruction approach based on Jacques Derrida's theory. The data source for this research is the novel Carita Calin by Aprilia Fatmawati and the fairy tale Bawang Merah Bawang Putih as the second data source. Data collection technique used is the technique of reading notes. Data analysis techniques using descriptive analysis techniques. The results of this research work are, (1) opposing the binary character Calin in the novel Carita Calin by Aprilia Fatmawati which presents contradictory things that are different from the tales of Bawang Merah Bawang Putih. (2) The new construction in the novel Carita Calin by Aprilia Fatmawati presents a character with a reversal of facts in the story of Bawang Merah Bawang Putih, Calin is not completely evil, Calin and Mora end up getting along as siblings, her mother spoils Mora more than she does, and Calin is the dominant character in the novel story.